2018
DOI: 10.3847/2041-8213/aad180
|View full text |Cite
|
Sign up to set email alerts
|

Objective Lagrangian Vortex Detection in the Solar Photosphere

Abstract: Vortices in the solar photosphere can be linked to a wide range of events, such as small-scale solar eruptions, wave excitation, and heating of the upper part of the solar atmosphere. Despite their importance in solar physics, most of the current studies on photospheric vortices are based on methods that are not invariant under time-dependent translations and rotations of the reference frame and are Eulerian; i.e., they are based on single snapshots of a velocity field and, therefore, do not convey information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…For a finite time duration [t 0 , t 0 + τ], a Lagrangian vortex is defined as an evolving material domain filled with a nested family of convex tubular level surfaces of LAVD t 0 +τ t 0 with outward-decreasing LAVD values. In contrast to the Eulerian methods that detect instantaneous swirl-like structures that do not convey long-term information of fluid motions, it was demonstrated that the LAVD method is capable of detecting persistent vortical flows (Haller et al 2016;Rempel et al 2017;Silva et al 2018). For 2D incompressible, shearless, non-magnetized fluids, the center of objective vortices are usually co-spatial with a local maximum of the LAVD field (Haller et al 2016).…”
Section: Elliptic Lagrangian Coherent Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…For a finite time duration [t 0 , t 0 + τ], a Lagrangian vortex is defined as an evolving material domain filled with a nested family of convex tubular level surfaces of LAVD t 0 +τ t 0 with outward-decreasing LAVD values. In contrast to the Eulerian methods that detect instantaneous swirl-like structures that do not convey long-term information of fluid motions, it was demonstrated that the LAVD method is capable of detecting persistent vortical flows (Haller et al 2016;Rempel et al 2017;Silva et al 2018). For 2D incompressible, shearless, non-magnetized fluids, the center of objective vortices are usually co-spatial with a local maximum of the LAVD field (Haller et al 2016).…”
Section: Elliptic Lagrangian Coherent Structuresmentioning
confidence: 99%
“…This is not necessarily true for highly compressible magnetized fluids with strong shear regions such as photospheric flows, for which we must allow some deviation from convexity to ensure that all vortex cores are captured. Moreover, Silva et al (2018) showed that in order to avoid false vortex detection in flows with strong shear, such as supergranulations, it is necessary to apply a postprocessing filter to the set of vortices detected by LAVD. The d-criterion, based on the geometry of the streamlines of the displacement vector field of fluid elements, is adopted to find vortex cores.…”
Section: Elliptic Lagrangian Coherent Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Since IACD is based on the curl of B, it will be large on regions with rotation of magnetic field lines as well as shear regions, a problem shared with the LAVD operator in velocity fields. For a discussion on problems related to kinematic vortex detection in strong shear regions of observational velocity fields using LAVD, as well as possible solutions to these problems, see Silva et al [26].…”
Section: Deterministic Initial Conditions: Orszag-tang Vortexmentioning
confidence: 99%